2022
DOI: 10.4209/aaqr.210351
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Strategic Mobility Restrictions Policies during 2020 COVID-19 Outbreak on Brazil’s Regional Air Quality

Abstract: With the unexpected arrival of the COVID-19 pandemic, countries worldwide were forced to take measures to curb its transmission. Mobility restrictions policies were the primary preventive measures applied around the globe. In addition to reducing the disease spread, they resulted in air quality changes in urbanized areas. In this sense, this study aimed to investigate how the mobility restrictions imposed by public policies impacted the air quality in Brazil during the COVID-19 2020 outbreak. Therefore, air qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 74 publications
(103 reference statements)
0
13
0
Order By: Relevance
“…Therefore, although many studies have already conducted quality assessments for multiple satellite data in China, the USA, and some European countries ( He et al, 2017 ; Ialongo et al, 2020 ; Liu et al, 2019 ; Nichol and Bilal, 2016 ; Tack et al, 2021 ; Verhoelst et al, 2021 ), there is still a need for regionalized evaluations in areas with distinctive local characteristics. In this context, the sharp drops in air pollutant levels observed during the COVID-19 outbreak ( Collivignarelli et al, 2020 ; Gkatzelis et al, 2021 ; Nakada and Urban, 2020 ; Rudke et al, 2021 , Rudke et al, 2022 ) can configure an ideal scenario to evaluate the performance of satellite remote sensing in capturing surface air quality variability.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, although many studies have already conducted quality assessments for multiple satellite data in China, the USA, and some European countries ( He et al, 2017 ; Ialongo et al, 2020 ; Liu et al, 2019 ; Nichol and Bilal, 2016 ; Tack et al, 2021 ; Verhoelst et al, 2021 ), there is still a need for regionalized evaluations in areas with distinctive local characteristics. In this context, the sharp drops in air pollutant levels observed during the COVID-19 outbreak ( Collivignarelli et al, 2020 ; Gkatzelis et al, 2021 ; Nakada and Urban, 2020 ; Rudke et al, 2021 , Rudke et al, 2022 ) can configure an ideal scenario to evaluate the performance of satellite remote sensing in capturing surface air quality variability.…”
Section: Introductionmentioning
confidence: 99%
“…Although the empirical evidence reported so far indicates large benefits and improvements in the reduction in the concentration of particulate pollutants, in the USA particulate matter such as PM 2.5 did not report significant decreases (Archer et al 2020 ). In the case of Brazilian cities, decrease in PM 10 and PM 2.5 levels (Rudke et al 2022 ) were reported, and in Andalusia (southern Spain), a slight reduction in PM 10 levels was also reported (Millán-Martínez et al 2022 ), due to transport mobility restrictions. In the old continent, large decreases are also reported as a result of mobility restrictions.…”
Section: Introductionmentioning
confidence: 97%
“…One of the goals formulated is to move towards the development of sustainable cities and communities, and one aspect of this goal is the transition to sustainable mobility and improvements in air quality in large metropolises (ONU 2017a ). Under this logic, different initiatives have been promoted that seek to promote and measure urban sustainability (Merino-Saum et al 2020 ; He et al 2018 ), improve energy infrastructure (Futcher et al 2017 ), promote sustainable mobility (Nikitas et al 2021 ; Celata and Sanna 2019 ; Sdoukopoulos et al 2019 ; Mozos-Blanco et al 2018 ) and electro-mobility ( Cansino et al 2018 ; Pisoni et al 2019 ; Tucki et al 2019 ; Pietrzak and Pietrzak 2020 ; Sofia et al 2020 ; Urrutia-Mosquera and Fábrega 2021 ), and improve air pollution levels by reducing the concentration levels of PM 2.5 and PM 10 that is emitted by urban transport (Rudke et al 2022 ; Holnicki et al 2021 ; Mądziel et al 2021 ; Garling 1998 ).…”
Section: Introductionmentioning
confidence: 99%
“…Restrictions on outdoor activities and travel, including strict health and safety protocols and lockdowns imposed by governments of the countries to contain the pandemic, significantly reduced the vehicular traffic and industrial and commercial activities globally since the beginning of 2020 (Jephcote et al, 2021;Madineni et al, 2021;Yang et al, 2021;Zhang et al, 2020). Those restrictions affected air quality in urban and commercial areas around the world (Dasgupta and Srikanth, 2020;Rudke et al, 2022;Sannigrahi et al, 2021). Several recent studies have shown that COVID-19-related restrictions and lockdowns resulted in reduced levels of air pollutants, such as particulate matter (PM), nitrogen dioxide (NO 2 ), and carbon monoxide (CO), whereas increased levels of ozone (O 3 ) in the atmosphere (Adam et al, 2021;Elsaid et al, 2021;Ghahremanloo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, lockdowns had varying degrees of impact on atmospheric concentrations of different air pollutants. For example, in Brazil, substantial reductions in CO (-53% in the State of Rio Grande do Sul), NO2 (-34% in Rio de Janerio), and PM 10 (-23% in Espírito Santo) concentrations, but an increase in O 3 concentration (40% in Paraná), were reported during the first month of the implementation of COVID-19related restrictions (Rudke et al, 2022). Similarly, in the UK, mean NO 2 and PM 2.5 levels decreased by 38.3% and 16.5%, respectively, whereas O 3 increased by 7.6% (Jephcote et al, 2021).…”
Section: Introductionmentioning
confidence: 99%